IMPROVEMENT OF THE SHORT-TERM STABILITY OF EMBANKMENT ON SOFT SOIL BY USING A GEOSYNTHETIC FABRIC WITH INSTALLED STONE COLUMNS - Faik Abbas Al-Wakel, Saad (Journal of Engineering and Sustainable Development, 2016)
In this study, the short-term stability of an embankment on soft has been improved by reinforcing the embankment with a geosynthetic fabric and reinforcing the foundation with stone columns. The behavior of the embankment is numerically modeled, and the finite element analysis for the reinforced embankment on soft clay (with and without stone columns) is presented. The principle of this improvement is that the geotextile as the geosynthetic fabric is used to increase the factor of safety for the short-term stability of the embankment, then the stone columns are used to maintain the side slope stability with a minimum factor of safety.